Lift-off free catalyst for metal assisted chemical etching of nanostructured silicon zone plates in vapour phase - Hanna Ohlin; Bryan Benz; Lucia Romano; Ulrich Vogt (Nano Express)
Metal-assisted chemical etching of silicon, especially in the vapour phase, is a highly promising technique for fabricating nanostructures with high aspect ratios. Here, a nanoscale pattern of x-ray zone plates written by electron beam lithography works as a mould for Pt electroplating on a Au seed layer to realise a nanostructured AuPt bilayer pattern on a silicon substrate. Our approach shows that the silicon etching induced by the electroplated catalyst occurs in a vapour of HF and oxygen, producing nanostructures with feature sizes as small as 10 nm, demonstrating that this catalyst synthesis method is suitable for vapour-based metal assisted chemical etching.